Improving body composition and strength in athletes through a 4-month combined martial arts and strength training program - Stachoń, Aleksandra; Burdukiewicz, Anna; Pietraszewska, Jadwiga; Andrzejewska, Justyna; Stefaniak, Tadeusz (Journal of Education, Health and Sport, 2016)
Stachoń Aleksandra, Burdukiewicz Anna, Pietraszewska Jadwiga, Andrzejewska Justyna, Stefaniak Tadeusz. Improving body composition and strength in athletes through a 4-month combined martial arts and strength training program. Journal of Education, Health and Sport. 2016;6(6):445-458. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56131 http://ojs.ukw.edu.pl/index.php/johs/article/view/3617 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 16.06.2016. Improving body composition and strength in athletes through a 4-month combined martial arts and strength training program 1Aleksandra Stachoń, 1Anna Burdukiewicz, 1Jadwiga Pietraszewska, 1Justyna Andrzejewska, 2Tadeusz Stefaniak 1Zakład Antropologii Fizycznej, Akademia Wychowania Fizycznego, ul. Paderewskiego 35, Wrocław 2Zakład Sportów Indywidualnych, Akademia Wychowania Fizycznego, ul. Paderewskiego 35, Wrocław Corresponding author: Dr Aleksandra Jadwiga Stachoń, e-mail: aleksandra.stachon@awf.wroc.pl Departament of Physical Anthropology, University School of Physical Education in Wrocław, al. I.J. Paderewskiego 35, bud. P2, 51-612 Wrocław; Poland Phone: 71 347 33 44 Key words: resistance training, body build, body composition, combat sport. Abstract Background and aim. Body composition is one of key components of health in both general and athletic populations. In martial arts great significance is attached to the development of mesomorphy and strength, which are crucial for performing offensive and defensive actions during fights. The study proposes to introduce progressive strength training programme - arranged primarily for beginners – in order to improve body composition of non-elite male martial arts competitors. The present study aims to evaluate the changes in body massiveness, body composition and strength in 31 martial arts practitioners from academic sports clubs after a combined martial arts and strength training programme. Material and methods. The 16-week intervention was based on a targeted progressive resistance training protocol developed by Stefaniak [1995]. The anthropometric, physical and motoric measurements were performed twice at four months interval. This programme includes training three times weekly with increased number of repetitions (19-24), number of sets (1-3) and increased loads (5%). Results. After the completion of the training program, significant increase for about 1.8 kgin body mass was observed. Body massiveness (BMI) increased from 23.2 ± 1.8 kg/m2 to 23.9 ± 1.8 kg/m2. The analysis using Sheldon’s somatotypes revealed an increase of mesomorphy (from 5.5 to 5.7) and decrease of ectomorphy (from 2.5 to 2.4). The level of endomorphy became stable (2.1). The maximal circumferences of flexed arm, forearm, calf and thigh increased significantly of about 0.6-1.2 cm. The amount of fat mass remained unchanged, but the amount of fat free mass and muscle mass increased about1.5 kg (MM from 43.7 ±4.8 kg to 45.3 ±5.5 kg). Back muscle strength increased of10.0 kg. In left hand there was visible increase of grip strength, whereas right hand grip strength became stable. Conclusions. The results of the present study indicate that even experienced but non-elite academic male martial artists could improve their body composition and muscle strength by completing the proposed strength training programme together with martial arts training. The effect of symmetrization in hand grip strength is beneficial for sport performance and everyday movements practice.